2014
DOI: 10.1177/0734242x14562660
|View full text |Cite|
|
Sign up to set email alerts
|

Removal performance of elemental mercury by low-cost adsorbents prepared through facile methods of carbonisation and activation of coconut husk

Abstract: The preparation of chars and activated carbon as low-cost elemental mercury adsorbents was carried out through the carbonisation of coconut husk (pith and fibre) and the activation of chars with potassium hydroxide (KOH), respectively. The synthesised adsorbents were characterised by using scanning electron microscopy, Fourier transform infrared spectroscopy and nitrogen adsorption/desorption analysis. The elemental mercury removal performance was measured using a conventional flow type packed-bed adsorber. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, materials used for preparation of higher quality activated carbon cost greater [12]. Searching for low cost activated carbon resources is of great importance in the removal of heavy metals from wastewater [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, materials used for preparation of higher quality activated carbon cost greater [12]. Searching for low cost activated carbon resources is of great importance in the removal of heavy metals from wastewater [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Johari et al conducted a column study of elemental mercury removal using coconut fiber and its activated char variants [105]. In the study, the coconut fiber adsorbent was first carbonized at 700 C as to convert the fibers into char materials.…”
Section: Coconut Fibermentioning
confidence: 99%
“…Table 3 shows that Johari et al and Saman et al have conducted comprehensive studies on determining the adsorptive capabilities of the coconut pith in removing mercury ions, methylmercury, and elemental mercury. Johari et al conducted a column elemental mercury removal using coconut pith as adsorbent source for activated char adsorbent [105]. In the study, the coconut pith was carbonized and subsequently was treated and activated with KOH solution.…”
Section: Coconut Pithmentioning
confidence: 99%
“…The thermodynamic studies also indicated that the process was spontaneous, feasible, and endothermic. Several other recent and relevant studies reported on mercury adsorption using different adsorbents are discussed …”
Section: Purification Of Mercury‐containing Wastewater Using Low‐costmentioning
confidence: 99%